Does surgical treatment within 4 hours after trauma have an influence on neurological remission in patients with acute spinal cord injury? - Biglari B; Child C; Yildirim TM; Swing T; Reitzel T; Moghaddam A (Dove Medical Press, 2016)
Bahram Biglari,1 Christopher Child,2 Timur Mert Yildirim,2 Tyler Swing,2 Tim Reitzel,1 Arash Moghaddam2 1Department of Paraplegiology and Technical Orthopedics, BG Trauma Centre, Ludwigshafen, Germany; 2Heidelberg Trauma Research Group, Center for Orthopedics, Trauma Surgery and Spinal Cord injury, Heidelberg University Hospital, Heidelberg, Germany Background: The proper timing for surgery in patients with acute spinal cord injury is controversial. This study was conducted to detect if there is an advantage in early (within the first 4 hours after trauma) compared to late (between 4 and 24 hours after trauma) surgery on neurological outcome.Methods: In this single institution prospective cohort study, data were analyzed from 51 spinal cord injured patients with an average age of 43.4 (±19.2) years. The influence of early (29 patients within the first 4 hours) as opposed to late (22 patients between 4 and 24 hours) decompression was evaluated by comparing data for neurological outcome. Patients of the study collectively suffered acute spinal fractures from C2 to L3 (cervical 39.2%, thoracic 29.4%, and lumbal 21.6%) or nonosseous lesions (9.8%). American Spinal Injury Association (ASIA) Impairment Scale (AIS) grades were assessed at time of admission and 6 months after trauma or longer depending on the time of release. Surgical treatment included early stabilization and decompression within 24 hours.Results: No significant difference between improved neurological function, measured with the AIS, and an early or late surgery time can be seen (P=0.402). Furthermore, binary logistic regression shows no significant difference between sex or age, and AIS improvement as possible confounders.Conclusion: In our study, all patients with spinal cord injury were treated with spine stabilization and decompression within the first 24 hours after trauma. Surgical decompression within the first 4 hours after trauma was not associated with improved neurological outcome compared to treatment between 4 and 24 hours. In a clinical context, this indicates that there is a time frame of at least 1 day in which optimal care is possible. Keywords: spinal cord injury, surgery, neurological remission, neurological outcome, AIS